Transgenic Expression of the Vitamin D Receptor Restricted to the Ileum, Cecum, and Colon of Vitamin D Receptor Knockout Mice Rescues Vitamin D Receptor−Dependent Rickets - Dhawan, Puneet (Endocrinology, 2017)
Although the intestine plays the major role in 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] action on calcium homeostasis, the mechanisms involved remain incompletely understood. The established model of 1,25(OH)(2)D(3)-regulated intestinal calcium absorption postulates a critical role for the duodenum. However, the distal intestine is where 70% to 80% of ingested calcium is absorbed. To test directly the role of 1,25(OH)(2)D(3) and the vitamin D receptor (VDR) in the distal intestine, three independent knockout (KO)/transgenic (TG) lines expressing VDR exclusively in the ileum, cecum, and colon were generated by breeding VDR KO mice with TG mice expressing human VDR (hVDR) under the control of the 9.5-kb caudal type homeobox 2 promoter. Mice from one TG line (KO/TG3) showed low VDR expression in the distal intestine (<50% of the levels observed in KO/TG1, KO/TG2, and wild-type mice). In the KO/TG mice, hVDR was not expressed in the duodenum, jejunum, kidney, or other tissues. Growth arrest, elevated parathyroid hormone level, and hypocalcemia of the VDR KO mice were prevented in mice from KO/TG lines 1 and 2. Microcomputed tomography analysis revealed that the expression of hVDR in the distal intestine of KO/TG1 and KO/TG2 mice rescued the bone defects associated with systemic VDR deficiency, including growth plate abnormalities and altered trabecular and cortical parameters. KO/TG3 mice showed rickets, but less severely than VDR KO mice. These findings show that expression of VDR exclusively in the distal intestine can prevent abnormalities in calcium homeostasis and bone mineralization associated with systemic VDR deficiency.